Profit Sharing Principle: Philosophical and Practical Basis of Mudharabah and Musyarakah - Myla Lestari; Saigatun Haniyah; Sri Rokhlinasari; Alvien Septian Haerisma (Danadyaksa: Post Modern Economy Journal, 2026)
This study examines the differences between mudharabah and musyarakah contracts and their implications for Islamic banking practices. Using a qualitative approach with a literature review method, the study analyzes data obtained from scientific journals, books, and related academic sources through descriptive and comparative analysis. The discussion focuses on key aspects of both contracts, including capital contribution, business management, profit-sharing mechanisms, and risk distribution. The findings indicate that mudharabah provides greater flexibility because business management is fully entrusted to the entrepreneur. However, this contract is more vulnerable to information asymmetry, moral hazard, and monitoring difficulties, which increase the level of financing risk. In contrast, musyarakah offers a more balanced partnership model through direct involvement of all parties in business management and decision-making, resulting in stronger control and more manageable risks. Consequently, musyarakah has become more widely applied in Islamic banking practices due to its stability and suitability for modern financing systems. The study also reveals a gap between the theoretical ideal of profit-sharing contracts and their practical implementation in Islamic financial institutions. Although mudharabah conceptually reflects a higher level of trust and partnership, its application remains limited because Islamic banks tend to prioritize financing models with lower operational risks. Meanwhile, musyarakah is considered more adaptable to contemporary banking needs due to its balance between profitability, supervision, and financial stability. Therefore, the study emphasizes the importance of strengthening supervision mechanisms, improving transparency, and developing innovative contract models to optimize the implementation of profit-sharing principles in the Islamic financial system.